Studi Pustaka : Perspektif Filsafat Aksiologi pada Transplantasi Terumbu Karang dalam Upaya Rehabilitasi Ekosistem Perairan Laut - Dwi Sulistyono; Muh. Ulit; Hasim Hasim (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to examine the perspective of axiological philosophy on coral reef transplantation in an effort to rehabilitate marine ecosystems. Philosophy plays an important role in mapping the flow of human thought in formulating the intended goals. The branch of axiological philosophy also describes the benefits and values ​​of an object to be studied. Coral reef ecosystems have an important function in the sustainability of marine life. However, there are various threats faced by these ecosystems. As an effective solution, transplantation needs to be studied and explored for its values ​​and benefits. The study uses a literature study method by reviewing 25 scientific articles related to coral reef transplantation and environmental axiology. Through this literature study, the findings of axiological philosophical values ​​​​in coral reef transplantation include ethical values, aesthetic values, and practical (instrumental) values. This study also describes the axiological dimension in a larger context, namely towards marine conservation which includes moral values, aesthetic values, and usefulness values. The results of this study are expected to provide an overview and strengthen information on the importance of coral reef transplantation as a concrete step in efforts to rehabilitate marine ecosystems.